THE QUESTIONS OF THE RATIONAL EFFICIENT USE RESURSNOGO POTENTIAL IN CONTEXT OF THE IMPROVEMENT TO TERRITORIAL ORGANIZATION PRODUCTION (ON EXAMPLE SOUTH ARAL REGION) (Academia Science Repository, 2023)
In article is considered questions of the complex use natural-economic potential in context improvement to territorial organization of the branches production in administrative region lower reached Amudarii in order to increase in market conditions.